Fenomenologi Kenakalan Remaja Punk - Noor, Romay; Sujarwo, Sawi (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2018)
This study dercribes to determine the depth of the juvenile delinquency punk. To achieve these objectives the researchers used a qualitative method with phenomenological approach and a case study approach. Subjects examined in this study was a 19 years old young men and one young woman was 19 years old. Based on the research results, forms of juvenile delinquency conducted first subject leads to criminal acts such as extortion, theft, becoming the sedative dealers and drug couriers, out of prison-related cases of aggravated assault and possession of sedatives illegally, sexual violence, and even perform murder. While the second subject just plain mischief that have not led to a criminal act. Factors causing juvenile delinquency punk conducted two subjects because of the influence of social environment, family environment that is not harmonious, music punk they hear, and there is a push from the inside of the subject to perform naughtiness which has been a problem for both subjects